Experimental study on the indentation of epoxy resin–aluminum honeycomb composite sandwich panel. Issue 9 (3rd May 2021) - Xin, Yajun; Yan, Huiming; Yang, Shuo; Li, Huijian; Cheng, Shuliang
Abstract: The present study develops a new type of epoxy resin–aluminum honeycomb composite sandwich panel. Failure modes and typical force–displacement curves are measured through quasi-static localized indentation tests. The effects of different parameters on the elastic ultimate load and energy absorption are analyzed. The results indicate that the newly developed composite sandwich panel has good integrality, stability, and energy absorption capacity. The typical force–displacement curve exhibits three types and all of them consist of six phases, namely: elastic phase, local damage phase, strengthening phase, global damage phase, compaction phase, and bottom destruction phase. The strength and the energy absorption capacity of the composite sandwich panel are affected by composite layer thickness, additional layer thickness, boundary condition, and indenter type. Compared to those of traditional sandwich panel, the mechanical properties of the integrated composite sandwich panel are significantly improved, as the specimen maintains good stability under indentation without undergoing detachment or cracking between the composite layer and the core.